Analisis Motivasi dan Kinerja Karyawan Klinik Swasta di Kabupaten Lumajang Berdasarkan Kompensasi Yang Diberikan - Ermawati, Emmy; Barlian, Noer Aisyah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
This study aims to identify the effects of direct compensation, indirect compensation and non-financial compensation on the motivation and performance of employees of private health clinics. The population of this research is private clinic employee in Lumajanga Regency with 34 respondents used as sample. Data analysis technique used multiple linear regression analysis. The results of this study indicate that partially all variables have no significant effect on motivation and performance. While simultaneously the three variables only have a significant effect on motivation but not on employee performance. In addition, this study indicates that motivation has a significant effect on employee performance. Coefficient of determination for motivation variable equal to 58,9% which means this variable can be explained by three independent variable in this research. This is different from the performance variable which is only 14.2%. As for the influence of motivation on the performance of coefficient of determination of 14.2%. Furthermore, this research is expected to contribute in the development of management science studies, especially human resource management so that it can become a reference for further research